Chimeric antigen receptor T-cells: a review on current status and future directions for relapsed/refractory multiple myeloma - Hamadeh, Issam S.; Friend, Reed; Mailankody, Sham; Atrash, Shebli (Frontiers in Oncology, 2024)
Although multiple myeloma is an incurable disease, the past decade has witnessed significant improvement in patient outcomes. This was brought about by the development of T-cell redirection therapies such as chimeric antigen receptor (CAR) T-cells, which can leverage the natural ability of the immune system to fight myeloma cells. The approval of the B-cell maturation antigen (BCMA)-directed CAR T, idecabtagene vicleucel (ide-cel), and ciltacabtagene autoleucel (ciltacel) has resulted in a paradigm shift in the treatment of relapsed/refractory multiple myeloma.Overall response rates ranging from 73 to 97% are currently achievable. However, the limitations of KarMMa-1 and CARTITUDE-1 studies spurred the generation of real-world data to provide some insights into the effectiveness of ide-cel and cilta-cel among patients who were excluded from clinical trials, particularly those who received prior BCMA-targeted or other T-cell redirection therapies. Despite their unprecedented clinical efficacy in heavily pretreated patients, responses to CAR T remain non-durable. Although the underlying mechanisms of resistance to these agents haven't been fully elucidated, studies have suggested that resistance patterns could be multifaceted, implicating T-cell exhaustion and tumor intrinsic mechanisms such as BCMA target loss, upregulation of gamma-secretase, and others. Herein, we provide a succinct overview of the development of CAR T-cells, manufacturing process, and associated toxicities/complications. In this review, we also recapitulate the existing literature pertaining MM CAR-T as well as emerging data from some of the ongoing clinical trials designed to mitigate the shortcomings of these agents, and improve the clinical efficacy of CAR T, especially in the relapsed/refractory setting.